Isolation and characterization of an antifungal compound 5-hydroxy-7,4’-dimethoxyflavone from Combretum zeyheri - Mangoyi, Rumbidzai (BMC Complement Altern Med, 2015)
BACKGROUND: Combretum zeyheri, belongs to the family Combretaceae and is one of the most popular herbal plants in tropical and subtropical countries. The leaves of Combretum zeyheri have been used as herbal medicine and have been reported to have pharmacological activity which includes anti-bacterial, anti-fungal, anticancer and antioxidant properties. The goal of this study was to isolate, identify and characterize compounds from C. zeyheri leaves which are responsible for its antifungal activity. METHODS: The preliminary isolation of C. zeyheri active compounds was carried out using chromatographic techniques which include sephadex gel column chromatography, silica gel column chromatography and thin-layer chromatography (TLC). The isolated compounds were then investigated for their antifungal activity using broth dilution assay. The combined effect of the most potent compound and an antifungal drug miconazole was investigated using the checkerboard assay. Time-kill assays were conducted for the combinations using the colony counting method. The mechanism of action of 5-hydroxy-7,4’-dimethoxyflavone as a potent antifungal agent was investigated by determining its inhibitory activity on Candida albicans drug efflux pumps using the ciprofloxacin assay. The ability of 5-hydroxy-7,4’-dimethoxyflavone to inhibit antioxidant enzymes as well as the biosynthesis of ergosterol were also investigated. RESULTS: A total of four pure compounds (A-D) were isolated from C. zeyheri leaf extract. Compound B (5-hydroxy-7,4’-dimethoxyflavone) was found to be active against Candida albicans using broth dilution method. This compound was also found to have synergistic activity on growth of C. albicans when combined with miconazole, completely inhibiting growth after only 4 hrs of incubation. Analysis of ergosterol content from Candida albicans showed a time-dependent decrease to 91 % and 63 % at 16 and 24 hrs respectively, in cells treated with ½ MIC of 5-hydroxy-7,4’-dimethoxyflavone. The compound 5-hydroxy-7,4’-dimethoxyflavone also showed inhibition of both the drug efflux pumps (with IC(50) = 51.64 μg/ml) and the antioxidant enzymes (at 5 μM). CONCLUSION: The compound 5-hydroxy-7,4’-dimethoxyflavone may be partly responsible for the reported antifungal activity of C. zeyheri, and may serve as a potential source of lead compounds that can be developed as antifungal phytomedicines.